2004
DOI: 10.3928/01484834-20040901-08
|View full text |Cite
|
Sign up to set email alerts
|

RN to FNP: A Qualitative Study of Role Transition

Abstract: Registered nurses who return to school in a nurse practitioner program undergo role transition throughout the educational process and into the postgraduate period. This study examined the role transition that occurs in family nurse practitioner (FNP) students. A descriptive, qualitative design was used with in-depth telephone interviews of 9 female FNPs who had recently graduated. A conceptual model was generated that described the role transition from RN to FNP. Two phases of role transition occurred and were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
74
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(77 citation statements)
references
References 4 publications
2
74
0
1
Order By: Relevance
“…The notion of transition in any context is a dynamic process requiring periods of adjustment, development, and change (Chang, Gardner, Duffield, & Ramis, 2010;Heitz, Steiner, & Burman, 2004). The transition of NPs and advanced practice nurses is influenced by many factors, including educational preparation, nursing knowledge and skills, personal and professional expectations, support from the interprofessional healthcare team, personal attributes, and interpersonal relationships (Fleming & Carberry, 2011;Sullivan-Bentz et al, 2010).…”
Section: Transition From Rn To Npmentioning
confidence: 99%
“…The notion of transition in any context is a dynamic process requiring periods of adjustment, development, and change (Chang, Gardner, Duffield, & Ramis, 2010;Heitz, Steiner, & Burman, 2004). The transition of NPs and advanced practice nurses is influenced by many factors, including educational preparation, nursing knowledge and skills, personal and professional expectations, support from the interprofessional healthcare team, personal attributes, and interpersonal relationships (Fleming & Carberry, 2011;Sullivan-Bentz et al, 2010).…”
Section: Transition From Rn To Npmentioning
confidence: 99%
“…Brown and Olshansky (1997) described the first years of practice of primary care NP graduates as a process, in which a crisis in confidence and competence associated with taking on a new position may lead to anxiety. Kelly and Mathews (2001) and Heitz, Steiner, and Burman (2004) described similar findings for NPs working in hospitals and for family NPs, respectively. Taking on a new role can be seen as a transition with profound changes in role relationships, expectations, and abilities.…”
mentioning
confidence: 69%
“…These subcategories were incremental in nature and emphasized the complex issues involved during transition (Brown & Olshansky, 1997). Brown and Draye (2003) and Heitz, Steiner, and Burman (2004) reported that some NPs experienced initial resistance to their roles by physicians and other nurses. These NPs felt betrayed and isolated as they had left traditional nursing for their new role.…”
Section: Discussionmentioning
confidence: 99%